2020
DOI: 10.1073/pnas.2017841117
|View full text |Cite
|
Sign up to set email alerts
|

Environmental noise degrades hippocampus-related learning and memory

Abstract: The neural mechanisms underlying the impacts of noise on nonauditory function, particularly learning and memory, remain largely unknown. Here, we demonstrate that rats exposed postnatally (between postnatal days 9 and 56) to structured noise delivered at a sound pressure level of ∼65 dB displayed significantly degraded hippocampus-related learning and memory abilities. Noise exposure also suppressed the induction of hippocampal long-term potentiation (LTP). In parallel, the total or phosphorylated levels of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 69 publications
2
34
0
Order By: Relevance
“… 15 The hippocampus is a key anatomical brain region involved in learning and memory, anxiety, and depression. 16 It is highly susceptible to drugs and environmental toxins. 17 A structural magnetic resonance imaging study found that a decreased volume of the hippocampal cortex and structural brain abnormalities were strongly associated with aggressive behavior.…”
Section: Introductionmentioning
confidence: 99%
“… 15 The hippocampus is a key anatomical brain region involved in learning and memory, anxiety, and depression. 16 It is highly susceptible to drugs and environmental toxins. 17 A structural magnetic resonance imaging study found that a decreased volume of the hippocampal cortex and structural brain abnormalities were strongly associated with aggressive behavior.…”
Section: Introductionmentioning
confidence: 99%
“…This is closely associated with anxiety-like behavior but not with short-term memory impairment. Given that previous reports have shown memory impairment following either 3 months of post-acute noise exposure ( Liu et al., 2018 ) or chronic repetitive noise exposure ( Zhang et al., 2021 ), the 2-week observation period following acute noise exposure in our animal model may not be sufficient to reveal the development of a memory deficit. This difference between our study and previous studies presumably arises from disparities in the animal species (rats vs. mice), noise levels (circumstantial vs. traumatic), age (young vs. mature), and laterality (bilateral vs. unilateral).…”
Section: Discussionmentioning
confidence: 94%
“…The hippocampus is susceptible to changes in response to noise exposure, irrespective of whether the noise is benign or traumatic. Long-term environmental noise exposure during the postnatal period (65 dB SPL) diminishes LTP in the perforant path (PP)-DG synapses and impairs hippocampus-dependent memory function ( Zhang et al., 2021 ). Traumatic noise exposure (110–120 dB) also diminishes LTP in the CA3-CA1 and PP-DG networks, although the behavioral effects of such changes have not yet been studied ( Cunha et al., 2015 ; De Deus et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the age of exposure seems to be a determining factor of how noise can affect the HC: it has been shown that noiseinduced hippocampal oxidative alterations in postnatal day 7 animals, should be generated through the activation of an auditoryindependent pathway, such as the mechanical vibration of the tissues (Molina et al, 2016a(Molina et al, , 2019, given that the auditory system of rats matures and becomes susceptible to sounds at approximately postnatal day 12. Finally, Zhang et al (2020) observed hippocampal and behavioral disturbances after chronic exposure to noise of about 65 dB, intensity considered non-stressful and not harmful to the auditory system. It should be noted that exposed animals were going through critical periods for development of the HC, which would make them more vulnerable to the noxious effects of noise.…”
mentioning
confidence: 89%
“…It should be noted that the auditory pathway is considered the main route through which loud noise can induce oxidative stress or excitotoxicity in HC; nevertheless, it is still not entirely clear how it occurs. On the one hand, it has been suggested that hearing loss would drive hippocampal dysfunctions (Nadhimi and Llano, 2020;Zhang et al, 2020). Indeed, in addition to HC damage, different alterations have been reported in the circuits that run between the auditory system and the HC.…”
mentioning
confidence: 99%